2007
DOI: 10.1089/dna.2006.0569
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Expression Analysis of a Protein Kinase C Gene, PKCμ, and Its Regulation of the Promoter Region in Zebrafish

Abstract: The cDNA and genomic DNA of zebrafish (Danio rerio) protein kinase Cmu (PKCmu), with its promoter region, were obtained. The 508-amino acid zebrafish PKCmu has 86.17% similarity to human PKCmu. Real-time reverse-transcription polymerase chain reaction analysis with starvation and hormonal treatment found significant differences between the control group and the experimental group after 14 days of starvation. After injecting insulin-like growth factor II (IGF-II), growth hormone (GH), insulin, or human chorioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Although the mechanisms of PKD1 activation have been investigated in many model systems, very little is known about its transcriptional regulation (Chen et al 2007, Rykx et al 2003). Our study is the first to characterize the mouse Prkd1 promoter and its activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanisms of PKD1 activation have been investigated in many model systems, very little is known about its transcriptional regulation (Chen et al 2007, Rykx et al 2003). Our study is the first to characterize the mouse Prkd1 promoter and its activity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that PKD1 plays a neuroprotective role in dopaminergic neurons during the early stages of oxidative stress (Asaithambi et al 2011(Asaithambi et al , 2014. Although the mechanisms of PKD1 activation have been investigated in many model systems, very little is known about its transcriptional regulation (Rykx et al 2003;Chen et al 2007). Our study is the first to characterize the mouse Prkd1 promoter and its activity.…”
Section: Discussionmentioning
confidence: 99%